The Effects of Dipeptidyl Peptidase 4 Inhibitors on Renal Function in Patients with Type 2 Diabetes Mellitus - Hsu, Wan-Chia; Lin, Chun-Sheng; Chen, Jung-Fu; Chang, Chih-Min (Journal of clinical medicine, 2022)
Past studies have confirmed that glucagon-like peptide 1 (GLP-1) receptor agonists can improve renal outcomes in patients with type 2 diabetes mellitus (DM). This study aimed to evaluate whether dipeptidyl peptidase 4 (DPP-4) inhibitors, which elevate GLP-1 levels, also have similar effects on renal function. In this retrospective study, diabetic patients treated with anti-hyperglycemic agents between 2008 and 2011 were selected. We compared the time to first occurrence of estimated glomerular filtration rate (eGFR) decline ≥30% from the baseline between patients treated with DPP-4 inhibitors and those treated with other anti-hyperglycemic drugs. A total of 2202 patients were enrolled. The incidence of eGFR decline ≥30% from the baseline was 10.08% in the DPP-4 inhibitor group and 16.17% in the non-DPP-4 inhibitor group (p < 0.001). The mean time to event was significantly longer in patients receiving DPP-4 inhibitors (2.84 ± 1.60 vs. 1.96 ± 1.30 years, p < 0.001). Patients who were younger than 65 years old, had better baseline eGFR, did not have preexisting hyperlipidemia, or who were untreated with concomitant statin showed greater reductions in the risk of renal function decline (all p for interaction < 0.05). Conclusively, DPP-4 inhibitors used alone or in combination with other glucose-lowering agents were correlated with lower risks of eGFR decline in patients with type 2 DM.